Guidance for Implementing Best Practice Therapeutic Exercise for Patients With Knee and Hip Osteoarthritis: What Does the Current Evidence Base Tell Us?. Issue 12 (10th December 2021) - Holden, Melanie A.; Button, Kate; Collins, Natalie J.; Henrotin, Yves; Hinman, Rana S.; Larsen, Jesper B.; Metcalf, Ben; Master, Hiral; Skou, Søren T.; Thoma, Louise M.; Wellsandt, Elizabeth; White, Daniel K.; et al.
Abstract : Therapeutic exercise is a recommended first‐line treatment for patients with knee and hip osteoarthritis (OA); however, there is little specific advice or practical resources to guide clinicians in its implementation. As the first in a series of projects by the Osteoarthritis Research Society International Rehabilitation Discussion Group to address this gap, we aim in this narrative review to synthesize current literature informing the implementation of therapeutic exercise for patients with knee and hip OA, focusing on evidence from systematic reviews and randomized controlled trials. Therapeutic exercise is safe for patients with knee and hip OA. Numerous types of therapeutic exercise (including aerobic, strengthening, neuromuscular, mind‐body exercise) may be utilized at varying doses and in different settings to improve pain and function. Benefits from therapeutic exercise appear greater when dosage recommendations from general exercise guidelines for healthy adults are met. However, interim therapeutic exercise goals may also be useful, given that many barriers to achieving these dosages exist among this patient group. Theoretically‐informed strategies to improve adherence to therapeutic exercise, such as patient education, goal‐setting, monitoring, and feedback, may help maintain participation and optimize clinical benefits over the longer term. Sedentary behavior is also a risk factor for disability and lower quality of life in patients with knee and hip OA, although limited evidence exists regarding how best to reduce this behavior. Current evidence can be used to inform how to implement best practice therapeutic exercise at a sufficient and appropriate dose for patients with knee and hip OA.